2021
DOI: 10.1089/neu.2021.0200
|View full text |Cite
|
Sign up to set email alerts
|

Network Analysis of Neurobehavioral and Post-Traumatic Stress Disorder Symptoms One Year after Traumatic Brain Injury: A Veterans Affairs Traumatic Brain Injury Model Systems Study

Abstract: Traumatic brain injury (TBI) is often experienced under stressful circumstances that can lead to symptoms of posttraumatic stress disorder (PTSD) and neurobehavioral symptoms of brain injury. There is considerable symptom overlap in the behavioral expression of these conditions. Psychometric network analysis is a useful approach to investigate the role of specific symptoms in connecting these two disorders and is well-suited to explore their interrelatedness. This study applied network analysis to examine the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 68 publications
0
13
0
Order By: Relevance
“…Some scholars argue that the features of psychopathy may represent robustly connected symptoms, which co-occur mainly due to their propensity to influence and reinforce each other, rather than reflect a common latent factor (Verschuere et al, 2018). As such, PNA is an ideal framework through which to examine psychopathy because it has yielded novel insights into complex disorders such as traumatic brain injury and posttraumatic stress disorder (Klyce et al, 2021; Armour et al, 2017). Centrality estimates can be considered alongside estimates from analyses using a latent variable approach to provide complimentary, yet distinct, psychometric information (Marsman et al, 2018).…”
Section: Psychometric Network Analysismentioning
confidence: 99%
“…Some scholars argue that the features of psychopathy may represent robustly connected symptoms, which co-occur mainly due to their propensity to influence and reinforce each other, rather than reflect a common latent factor (Verschuere et al, 2018). As such, PNA is an ideal framework through which to examine psychopathy because it has yielded novel insights into complex disorders such as traumatic brain injury and posttraumatic stress disorder (Klyce et al, 2021; Armour et al, 2017). Centrality estimates can be considered alongside estimates from analyses using a latent variable approach to provide complimentary, yet distinct, psychometric information (Marsman et al, 2018).…”
Section: Psychometric Network Analysismentioning
confidence: 99%
“…Their study found no differences in brain damage, measurements, or volumes between groups, but they managed to find that the treatment subjects had lower diffusivity in the anterior and posterior limbs of the internal capsule compared to the controls, and that resting-state functional connectivity displayed greater correlation and covariance in multiple networks in treatment cases, with alterations most visible in the visual network in per-protocol analyses (Matthews et al, 2019 ). Traumatic brain injury (TBI) is frequently induced by stressful conditions, which can result in symptoms of post-traumatic stress disorder (PTSD) and neurobehavioral symptoms of brain damage (Klyce et al, 2021 ). Daradkeh et al investigated the impact of pomegranate juice intake on nutritional and behavioral results following traumatic brain damage.…”
Section: Brainmentioning
confidence: 99%
“…In this view, symptoms are measured as individual, functioning components that play a distinct role within the context of a given pathology (e.g., traumatic brain injury; Klyce et al, 2021). Dynamic systems theory is thus distinct from a latent variable approach, such that the latter assumes individual symptoms are necessarily indicators of a common cause (i.e., latent factor).…”
Section: Psychometric Network Analysis (Pna)mentioning
confidence: 99%
“…The inclusion of theoretically relevant covariates (e.g., impulsivity facets in a network of psychopathy items) in partial correlation networks provides the potential for important insights into the structure of a given trait or disorder, as edges between items and covariates are not due to the covariation among items (e.g., Armour et al, 2017). The examination of variables at different conceptual levels (e.g., domains, facets) using PNA further allows for identification of the individual items most responsible for the associations commonly observed between latent factors (e.g., Klyce et al, 2021;West & Chester, 2021).…”
Section: Psychometric Network Analysis (Pna)mentioning
confidence: 99%
See 1 more Smart Citation